Teachers' experiences of critical thinking in classroom teaching at selected schools in Ipoh : a qualitative study - Amalina Munirah binti Mohamed Zabidi (Kulliyyah of Education, International Islamic University Malaysia, 2016)
Malaysia aims to produce critical thinkers by the year 2020 according to the Ministry of Education's new curriculum plan. This study was conducted to explore the teachers' experiences in implementing critical thinking in classroom teaching. The second purpose of this study was to determine the methods of critical thinking that the teachers used to teach the students to think critically in the classrooms. This ethnography study is to know in-depth about the teachers' experience of implementing critical thinking in classroom teaching. The selection of the participants (teachers) was by using purposive sampling. The officer at the District-level Education Office had chosen six teachers from the list of excellent teachers in Kinta Utara. The teachers were three each from primary school and another three from secondary school who teaches Science, Mathematics and English. Interviews were conducted and the findings in this study were that eight methods were used in implementing critical thinking in the classroom teaching. The eight methods were stimulation, motivation, encouragement, discussion, facilitating, justification of own understanding, comparing and reasoning. Findings from this study could benefit other researchers to further develop a module for the methods in teaching critical thinking in schools.